Biochemical and genetic characterization of European silver eels, Anguilla anguilla (Linnaeus, 1758), from the Comacchio lagoon (Italy). (22nd September 2015) - Isani, G.; Randi, E.; Rossi, B.; Fabbri, E.; Brunelli, F.; Carpenè, E.; Mucci, N.
Summary: The European eel Anguilla anguilla has declined significantly over recent decades, exceeding its safe biological limits and probably reaching a historical minimum (1% of the 1960 recruitment level). Twenty‐three migrating females at the IV stage of silvering were collected from the Comacchio lagoon (Northern Italy); they showed high levels of cholesterol and triglycerides, probably due to lipid accumulation before migration across the Atlantic Ocean. Electrophoretic patterns showed high amounts of putative α and β globulins, probably due to high concentrations of lipoproteins. Genetic results obtained from a total of 49 specimens (20 from the Comacchio lagoon and 29 from Val Dogà) agree with the panmixia hypothesis, lacking any genetic differentiation over time and space at neutral loci. In conclusion, despite the small sampling and the population decline in recent years, high levels of variability were recorded.